Evaluasi Pengembangan Usaha Ekonomi Produktif di Desa Sebangau Mulya Sekitar Kawasan Taman Nasional Sebangau - Tito Surogo; Revi Sunaryati; Masliani (Journal of Environment and Management, 2020)
Taman Nasional Sebagau (TNS) or Sebangau National Park has been now striving to provide optimal benefits for the community surrounding its area through productive economic business development program, as it did in one buffer village, namely Sebangau Mulya. This program aims to improve community welfare, and as a form of community involvement in preserving the TNS area. However, the success of the program remains questionable. This study aims, first, to examine the development of productive economic business programs in Sebangau Mulya Village. Second, to analyze the effect of such program on the welfare of villagers. The research sample was 40 villagers who received direct assistance from the program. This figure account for 10% of the villagers. Descriptive analysis and multiple linear regression were used to study the relationship of 7 independent variables, namely facilitators (X1), institutions (X2), human resources capacity (X3), skills and knowledge of human resources (X4), type of productive economic assistance (X5), counseling and training (X6) and supervision (X7) with 1 dependent variable, i.e. community welfare. The results show that the program has been providing positive benefits, marked by the increase of cattle and goats number, compared to those provided by TNS management five years before. In addition, the program has been successfully tying villagers and TNS management in maintaining and managing the area according to the planned agenda. The factors that partially influence the beneficiaries welfare is skills and knowledge (X4), which is amounting to 26.80%. Since the community in carrying out productive economic businesses is in accordance with their skills and knowledge so that they are able to develop ideal businesses with the environmental conditions of Sebangau Mulya Village. Other six factors have no significant effect on villagers’ welfare.